Semantika anglicizama u srpskom jeziku u registru mode (Philologia, 2021)
The Serbian language of today is swarming with anglicisms in all thematic registers. This paper deals with the semantics of anglicisms from the fashion register since the presence of words like fensi, in, luk, bikini and mejkap is all the more pronounced in Serbian. This paper examines the following: (a) the meaning of the anglicism with respect to the meaning of its English model, that is the number and scope of the transferred meanings, (b) the communicative justiﬁcation of anglicisms. The fact that 48٪ of anglicisms have the same meanings as their models and that 60٪ of them are communicatively unjustiﬁed, leads to the following conclusion: the presence of anglicisms in this register is primarily a psychological and a sociological phenomenon which has largely become a linguistic one since it affects the structure of the Serbian language.